Influence of Agro-Ecological Zones on African Indigenous Vegetables Insect Pests Diversity and Density in Western Kenya - Wawuda, M. A.; Gohole, L. S.; Yaninek, J. S. (Africa Environmental Review Journal, 2021)
The influence of agro-ecological zones on African indigenous vegetables (AIVs) insect pest diversity in western Kenya has been scarcely documented. It was therefore important to discover the effect of Agro-ecological zones on the AIVs insect pest population and diversity. This study inventoried insects found on amaranth (Amaranthus sp), spider plant (Cleome gynandra) and nightshade (Solanum nigrum) in western Kenya. A field survey was conducted in Homa Bay, Siaya, Kisumu, Busia, Kakamega, Uasin Gishu and Kisii counties where amaranth, spider plant and nightshade are commonly produced and consumed. The counties were then sub-divided into agro-ecological zones (AEZs). Data was subjected to both numerical descriptive analysis and one-way ANOVA. From the survey 66 (84.6%) out of the 78 total insect species collected were insect pests. Hemipterans were the most numerous, while coleopterans were the most diverse. Insect species diversity on the surveyed AIVs was as follows: spider plant> amaranth> nightshade. Aphids were the most important common pests with Aphis fabae and Myzus persicae found on all three AIVs among the six aphid species identified. The influence of Agro-ecological zones on each AIVs insect density was strong (p=<0.05). The highest insect population and diversity was found in locations characterized by highland equatorial climate while the lowest population and diversity was found in locations with hot and dry climate. The study therefore concluded that indeed agro-ecological zones influence insect pest population and diversity. Therefore, farmers should always consider their agro-ecological zones before deciding on which AIVs to produce in order to maximize production while minimizing input expenditures.